2015
DOI: 10.1016/j.bbmt.2014.11.677
|View full text |Cite
|
Sign up to set email alerts
|

Second Autologous Stem Cell Transplant: An Effective Therapy for Relapsed Multiple Myeloma

Abstract: Therapeutic options for patients with multiple myeloma (MM) whose disease has relapsed after a prior autologous stem cell transplant (ASCT) include an expanding armamentarium of novel agents, often combined with traditional chemotherapy, or a second ASCT, with no clear standard of care. We retrospectively analyzed the outcomes of 75 patients who underwent salvage melphalan-based ASCT for relapsed MM at Memorial Sloan-Kettering Cancer Center between 1995 and 2012. Conditioning was performed with melphalan 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
(33 reference statements)
2
20
0
1
Order By: Relevance
“…These three retrospective studies involved tandem transplants which makes drawing conclusions difficult in the non‐tandem transplant population. When used for second ASCT, MEL140 and MEL200 had similar progression free survival and OS …”
Section: Discussionmentioning
confidence: 94%
“…These three retrospective studies involved tandem transplants which makes drawing conclusions difficult in the non‐tandem transplant population. When used for second ASCT, MEL140 and MEL200 had similar progression free survival and OS …”
Section: Discussionmentioning
confidence: 94%
“…Although the overall survival of patients relapsing after 18 months is promising, the short PFS in this group suggests a poor graft‐vs.‐myeloma effect and the extended OS probably reflects effective relapse treatment after allo‐SCT with novel agents. For patients relapsing beyond 1.5‐2 yr after auto‐SCT, we generally recommend novel agent‐based therapy or, in case of transplant eligible patients, a second auto‐SCT .…”
Section: Discussionmentioning
confidence: 99%
“…The optimal PFS following first ASCT for consideration for SAT varies in the literature from as short as 12 months [15,21] to as long as 36 months [11] to be predictive of a PFS advantage following SAT and from as short as 9 months [16] to as long as 36 months [11] to be predictive of an OS advantage (Table 1). Other studies have shown a linear relationship between increasing PFS following first ASCT and PFS and OS advantages following SAT [15,21,22]. The only exception to this trend was a recent study by Tremblay et al [23], in which PFS after first ASCT was not found to be predictive of PFS or OS following SAT.…”
Section: Optimizing Outcomes Following Sat Which Patients Are Approprmentioning
confidence: 99%